(untitled) - Axtell, Roger E. (Hoboken, N.J., 2007)
International business and leisure travel etiquette expert Roger Axtell's bestselling Do's and Taboos books have helped hundreds of thousands of business travelers and tourists avoid the missteps and misunderstandings the world traveler can encounter. In Essential Do's and Taboos, Axtell shares the wisdom he has compiled over a lifetime of international experience.
Keywords: Business travel,Business etiquette,Kinh doanh du lịch,Phép xã giao kinh doanh